Growth performance and energetic metabolism of pacu, Piaractus mesopotamicus (Holmberg, 1887), fed diets supplemented with ammonium metavanadate - Takahashi, Leonardo Susumu; Baldan, Ana Paula; Urbinati, Elisabeth Criscuolo [UNESP] (Wiley-Blackwell, 2006)
Vanadium compounds mimic most of the metabolic effects of insulin, suggesting that it might be useful to improve utilization of dietary carbohydrate. This work evaluated the effect of dietary ammonium metavanadate (H(4)NO(3)V) on the growth performance and energy metabolism of pacu, an omnivorous South America characin. Two hundred and eighty-eight fish were distributed into four blocks according to the body weight (21.8 +/- 1.7, 28.5 +/- 2.0, 28.4 +/- 1.9, 35.7 +/- 1.9 g), stocked in 24 plastic tanks and fed twice daily with isonitrogenous and isoenergetic diets containing six levels of H(4)NO(3)V (0, 10, 50, 100, 300 and 1000 mg kg(-1)) for 60 days. Increasing levels of dietary ammonium metavanadate did not improve growth (P > 0.05), and the highest level of inclusion (1000 mg kg(-1)) reduced performance (P < 0.05). Blood glucose levels decreased (P < 0.05) in fish fed 300 and 1000 mg kg(-1) H(4)NO(3)V, but no differences were observed in other blood metabolites. A slight increase in muscle lipid content was observed in fish fed a diet containing 300 mg kg(-1) H(4)NO(3)V. Based on the results of this study, there is no benefit in supplementing pacu diets with metavanadate.
Keywords: carbohydrate metabolism; insulin; vanadium